:Gestión pedagógica en el aula: clima social escolar,desde la percepción de estudiantes y profesores del séptimo año de educación básica de los centros educativos Reina Silva de Suecia de la ciudad de Quito y Luis Godin de la parroquia de Yaruqui , provincia de pichincha , en el año lectivo 2011-2012 - Plaza Cuty, Byron Giovanny (2013)
The present investigation has had by objective know the pedagogical management and the social climate of classroom , like elements of measure and description of the environment in which develops the educational process of the students of the seventh year of basic education of the urban school “Reina Silvia of Sweden” and the rural school “ Luis Godin” . The instruments used were the questionnaires of Moos and Tricket (1969) to measure the climate of the classroom , in an Ecuadorian adaptation (2011).Questionnaire of evaluations and folders of observation to the pedagogical management of the educational , Ministry of Education of the Ecuador The results allowed to do comparisons between the two educational institutions urban and rural . The sample was of 35 students , 15 of the rural sector and 20 of the urban sector , two educational one of the urban sector and one of the rural sector. The application of the instruments help to identify the skills and educational competitions from the criterion of the own educational, students and researcher , and also facilitated to know the climate of classroom where develops the learning of the students investigated. Key